Users take shortcuts: Navigating dictionary entries - Lew, Robert (Afûk, 2010)
In the present paper we compare the effectiveness of two alternative meaning access facilitators in a monolingual learner’s dictionary: a Menu system, placed at the top of a monolingual entry; and a Shortcuts system, where the cues are distributed throughout the entry. We test the two entry formats on 90 Polish learners of English at two CEFR levels, A2 and B1. The task which triggers dictionary consultation is guided translation from English to Polish. Three outcome measures are evaluated: access time to sense, accuracy of sense selection, and translation accuracy. While Menus and Shortcuts turned up no difference in terms of consultation speed, the task success was significantly better in the Shortcuts condition. Sense selection accuracy was also better, though not significanly so, for the Shortcuts. The overall conclusion of our study is that Shortcuts are more user-friendly than Menus, although this may also depend on the form of the cues and the medium of presentation.
Keywords: dictionaries; entry navigation; data access; access facilitators